Perbandingan Indikator Kinerja Bank Dominasi Asing dan Dominasi Negara pada Bank yang Go Public di BEI - Sucianti, Sucianti; Naomi, Prima (Jurnal Manajemen, 2009)
The presence of the foreign banking ownership in Indonesia has resulting in pro and contra. In one side it’s worried that the ownership of foreign banking may create foreign domination, but in the other hand states that the ownership of foreign banking has brings the positive impact in the efficiency and stabilization of banking. Meanwhile, national bank which is manage by government are often to be said having bad performance. This research is purposed to see the differences of the finance & share performances between bank that was dominated by foreign capital and bank that was dominated by government. Seven banks are taken as sample in the study and categorized into categorizes mentioned above. They are also included emitten bank registered in BEI. The 2007 financial statements of the banks are used in this study to observe and compute the variables determining the performance of the banks. The variables are LDR, CAR, ROE, BOPO, PBR and PER. The calculation and analysis are entirely based on Kruskal Wallis test technique. The result of the study provided that there are no significant differences on those variables in both group of banking. It means that no differences of the finance and share performances between the two groups of bank.Kata kunci: LDR, CAR, ROE, BOPO, PBV, PER, Bank dominasi asing, Bank dominasi negara.